The Effect of Early Knowledge of Respiratory Syncytial Virus Positivity on Medical Decision Making and Throughput Time Within the Pediatric Emergency Department. Issue 3 (March 2020) - Schnell, Jessica; Schroeder, Lisa; Sinclair, Kelly; Patel, Lina; Dowd, Denise
Abstract : Objective: The aim of this study was to evaluate whether early knowledge of respiratory syncytial virus (RSV) positivity by rapid triage-based testing protocol improved emergency department (ED) throughput time and decreased ED ancillary testing and antibiotic administration. Methods: A retrospective cohort study was performed of ED patients aged 2 to 12 months, presenting November 1 to March 31 for the years 2008–2013. Included patients presented with fever and upper respiratory tract symptoms. Patients were excluded if they tested positive for influenza, had chronic underlying medical problems, or were admitted or transferred from an outside facility or if no RSV result was documented. The study group was compared with infants who tested negative for RSV by the triage-based protocol and were diagnosed as having (1) bronchiolitis and (2) a viral illness. Results: Of 899 patients tested for RSV within triage, the study included 713 (79%); 231 (35.3%) tested positive for RSV. When comparing children diagnosed as having bronchiolitis, there was no statistically significant difference between RSV positive and negative in ED throughput time, ED administered antibiotics, or chest radiographs, urine analyses, blood cultures, or lumbar punctures obtained. When comparing children diagnosed as having a viral illness, RSV-positive patients had less chest radiographs, urine analysis, and blood cultures performed. Conclusions: Identifying the virus responsible for bronchiolitis through a triage-based protocol does not decrease ED throughput time, antibiotic administration, or chest radiographs, urine analysis, or blood cultures obtained. In infants presenting with upper respiratory tract symptoms and fever, knowing RSV infectivity through a triage-based protocol does significantly decrease chest radiographs, urine analysis, and blood cultures obtained.